IDIOLOGI PATRIARKI YANG TERGAMBAR PADA ROMAN THE GIFT KARYA DANIELL STEEL SEBUAH KAJIAN FEMINISME - Wahyuni Wahyuni (Jurnal Basataka (JBT), 2020)
The purpose of this research is to describe patriarchal ideology of female characters depicted in the novel The Gift by Danielle Steel. The method used in this research is descriptive qualitative. The source of data in this research is novel The Gift By Danielle Steel. To analyze patriarchal ideology data, researcher used literary criticism of feminism. The result of the research the patriarchal ideology of female characters depicted in the novel The Gift By Danielle Steel in the form of action in the domestic sector and public sector namely oppression, discrimination and injustice. Some women surrender and realize that as children and as wife must obey the mommands of their husbands or father.